Total synthesis of naturally occurring 5,6,7- and 5,7,8-trioxygenated coumarins - Maes, Dominick (2008)
The synthesis of five naturally occurring polyoxygenated coumarins is described. It concerns two 5,6,7-trioxygenated coumarins, i.e., 6-hydroxy-5,7-dimethoxycoumarin (fraxinol) 1 and 5,6,7-trimethoxycoumarin 2, and three 5,7,8-trioxygenated coumarins, i.e., 8-hydroxy-5,7-dimethoxycoumarin (leptodactylone) 3, 5,7,8-trimethoxycoumarin 4 and 8-(3-methyl-2-butenyloxy)-5,7-dimethoxycoumarin (artanin) 5. Key feature of the synthetic pathway is the synthesis of suitable tetraoxygenated benzaldehydes, which are then converted to the corresponding coumarins via a Wittig reaction.